PERLINDUNGAN HUKUM BAGI PEREMPUAN KORBAN KEKERASAN PEREMPUAN AKIBAT PERNIKAHAN DINI BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Fathul Jannah Fachrudin (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTDomestic violence is every act against someone especially women which caused misery or physical, sexual, psychological suffering, or neglect of the household including threats to commit act, coercion, or deprivation of independence against the law within the household that often befall women (a wife). As for the factors that influence the occurrence of domestic violence are early-age marriage, economic, competition in the household, and gender inequality that is tend to place women in a lower position and less valuable. Legal protection for victims of violence has been regulated in Law No. 23 of 2004 concerning the Elimination of Domestic Violence involving a related role, namely the role of the Government, Courts, Police, and Society so that the victims can feel a sense of security both mindfully and physically, and from various threats from any party.Perpetrators of domestic violence can be sentenced under Law No. 23 of 2004 concerning the Elimination of Domestic Violence, if the evidence presented by the Public Prosecutor has been proven legitimate and convincing, and the Judge believes that the perpetrator was found guilty, it can be sentenced in the form of criminal sanctions in accordance with the forms of violence that have been committed.